The Discourse Marker Adapun in The Manuscripts of Taj al-Salatin: (Penanda Wacana Adapun dalam Manuskrip Taj Al-Salatin) (Jurnal Bahasa, 2020)
The aim of this paper is to examine the use of "adapun" as a discourse marker in the classical Malay manuscript Taj al-Salatin by Bukhari al-Jauhari. The text was written in the 16th century during the reign of Sultan Alauddin Ri'ayat Shah Sayyid al-Mukammil (1590-1604) in Acheh, as a guide for good governance based on the teachings of Islam. This study focuses on describing the function of the discourse marker "adapun" as a grammatical cohesive device, such as is proposed in the Cohesion Theory of Halliday and Hasan (1995). This analysis was carried out using occurrences of 'adapun' obtained from the Malay Concordance Project (MCP). The study finds that the 'adapun' plays a bigger role rather than just as a grammatical cohesive device.Keywords: discourse markers, cohesion, Taj al-Salatin, Cohesion Theory